Assessing the management student's entrepreneurial intentions: Role of entrepreneurship education and technology transfer - Wang, Zihan; Ortiz, Geovanny Genaro Reivan (Frontiers in Psychology, 2022)
Entrepreneurship education is considered as an important way to influence the competitiveness of any country or industry. Therefore, entrepreneurship education provides opportunities to progress to a more competitive educational environment. This paper examines the impact of students' entrepreneurship education in China on their entrepreneurial intentions. Perceived entrepreneurial capacity, education in entrepreneurship, and attitudes toward entrepreneurship are all factors in the model developed to predict entrepreneurial intention. Structured equation modeling (SEM) is being used to test 98 management students from various universities in China. The findings show that there is statistically significant and positive relationship among entrepreneurship learning, entrepreneurial attitude, entrepreneurship education, and management students' entrepreneurial intention. Perceived behavioral control and perceive social rule significantly improve management students' entrepreneurial intention. Moreover, technology transfer correlates statistically with students' entrepreneurial intentions. Thus, universities are being encouraged to offer entrepreneurial training modules to increase their students' entrepreneurial intent.